(untitled) (Ameghiniana, 2013)
This paper is devoted to the study of the palynological content of the Retamito coal deposit. This deposit is located on the eastern base of Las Crucecitas dam in Río del Agua, 4 km East from Pedernal vilIage, route 135, San Juan Province. It is suggested to use the name "Las Crucecitas" for this locality in order to find it easier in the field. The microflora is composed by 25 morphological species, helonging to the genera: Calamospora; Leiotriletes, Retusotriletes; Apiculiretusispora; Granulatisporites, Verrucosisporites; Aeanthotriletes; Apiculatasporites, Pustulatis porites: Irmosporites; Raistriekia; Convolutispora, Dictyotriletes Cristatisporites, Laevigatosporites y Florinites. Five species are new: Verrucosisporites crenulatus; Acanthotriletes menendezii; Dictyotriletes diversiluminis; Cristatisporites verrucosus and Florinites verrucosus. Two species have a wide distribution in the northern hemisphere: Apiculatasporites spinolistratus (Loose) Ibrahim 1933 and Laevigatosporites vulgaris Ibrahim 1933, from the Carboniferous of Europe and U.S.A. The bulk of the remaining palynomorphs allows to establish a close relation with the Lagares Formation microflora, from Paganzo, La Rioja Province, which has been dated as Namurian.